Perception of nurses of maternity and pediatric units about paternal care - Almeida, Bruna Silveira de (2015)
Doi: 10.5902/2179769213589 Objective: to raise awareness about the perception of nurses in maternity and pediatric units in relation to paternal care in the contemporary family. Method:  exploratory study with a qualitative approach. The participants were nurses working in maternity and pediatric units of a university hospital located in southern Rio Grande do Sul. Semi-structured interviews were carried out for data collection and data were analyzed through discursive text analysis. Results: two categories emerged from the analysis: "paternal care in the contemporary family" and "Nursing care: factors that influence the participation of men in childcare". Conclusions: respondents highlighted the gap between what is recommended by public policies and by scientific literature and the reality in health institutions.